Vaccine Cold Storage Design Based on Low Cost Material - Dwi Joko Suroso; Yaqsa Mayza (JST (Jurnal Sains dan Teknologi), 2026)
The problem addressed in this study lies in the high cost and dependence on electrical energy in conventional cold storage systems, which hinder vaccine distribution, particularly in remote areas. In addition, the limited capability of existing storage systems to maintain stable temperatures without electricity presents a major challenge in preserving vaccine quality during distribution. This study aims to analyze and evaluate the performance of a low-cost cold storage design based on locally available materials in maintaining optimal vaccine storage temperatures effectively without the use of electrical energy. This research is categorized as an engineering study employing a numerical simulation design using thermal modeling software. The research subject is the cold storage design, while the testing subject consists of simulation models utilizing material parameters such as Polyvinyl Chloride (PVC), Nitrile Butadiene Rubber (NBR), and dry ice. Data were collected through simulation and documentation methods, with research instruments including SketchUp and SimFlow software. Data analysis was conducted using a quantitative descriptive approach by interpreting the relationship between temperature, pressure, and time obtained from the simulation results. The findings indicate that the proposed cold storage design is capable of maintaining temperatures below 8°C for approximately ±2.92 hours without electricity. Therefore, it can be concluded that the developed design is effective as an alternative solution for short-term vaccine storage. The implications of this study highlight the potential application of simple and affordable technology to support vaccine distribution in areas with limited infrastructure.